Mobile (Self-)Socialization: The Role of Mobile Media and Communication in Autonomy and Relationship Development in Adolescence. Issue 6 (2nd November 2021) - Schnauber-Stockmann, Anna; Weber, Mathias; Reinecke, Leonard; Schemer, Christian; Müller, Kai; Beutel, Manfred; Stark, Birgit
ABSTRACT: Two of the most important developmental tasks in adolescence are developing autonomy and establishing relationships (i.e., friendships and romantic relationships). Self-socialization processes are relevant in mastering these developmental tasks. Mobile media are predestined as tools for such self-socialization: Their affordances—universality, private accessibility, and ubiquity—closely match the developmental needs of adolescents and no other media device is so deeply embedded in adolescents' daily lives. The present paper proposes a reciprocal relationship between mobile media and communication and mastery of developmental tasks. The results of a three-wave panel study ( N = 503) point to a marginal role of mobile media and communication in developing autonomy and establishing relationships. Still, results suggest that developmental achievements enable adolescents to make sensible use of mobile media and communication in response to their current developmental stage.